Türkiye’de hıristiyan olan müslümanlar : psiko-sosyolojik bir araştırma (1990-2010) - Zavalsız, Y. Sinan (My University, 2012)
There had been some people who converted to Christianity as a result of great increase in the amount of missionary activities in Turkey in 1990s. Our study contains former Muslims in Turkey that had converted to Christianity between the years 1990 and 2010. İn our research which is mainly comprised of fieldwork, we used the methodology of documentation as well as social distance, questionnaires and interviews and also 32 respondents had answered 87 questions and 84.4 % of interviews were conducted through voice recording. Our work, includes some personal information regarding the respondents’life. Likewise, the childhood and adulthood periods of informents and their relationships with religion in both periods are examined. In addition, the reasons behind their conversion from Islam to Christianity and the stage of conversion are investigated. Finally, the experinces after conversion period that were faced by those converts are described.
Keywords: Din Sosyolojisi; Hristiyanlık; İslam Dini